Prototypes Of Learning Physics Using Computer Assisted Instruction Method - Pandi Barita Nauli Simangunsong; Mamed Rofendy Manalu (Educare: Journal Educational and Multimedia, 2023)
The learning that is being carried out now is still conventional in that the teacher only stands in front of the class and records the material on the board while the students copy the notes written on the board into their notes. This results in the reduced achievement of students who tend to prefer playing rather than learning. An alternative solution is to create learning applications using computer media with the hope of being able to improve classroom learning such as increasing student achievement. CAI stands for Computer Assisted Instruction which means it is a computer system that can deliver instruction directly to recipients of information by interacting with programmed subjects. Computer-Assisted Instruction (CAI) has been developed recently and has proven its benefits to assist teachers in teaching and assisting students in learning.